2014
DOI: 10.5935/1415-2762.20140004
|View full text |Cite
|
Sign up to set email alerts
|

The quality of life of patients with hematological neoplasia undergoing chemotherapy

Abstract: Este estudo teve por objetivo analisar a qualidade de vida do paciente com neoplasia hematológica submetido à quimioterapia. Realizou-se pesquisa quantitativa a partir da aplicação do questionário genérico WHOQOL-bref. A amostra foi composta de 16 pacientes do setor de ambulatório de quimioterapia de alto risco de um hospital de ensino do município de Curitiba-PR, no período de fevereiro a abril de 2010. Os resultados evidenciaram a prevalência do sexo masculino e a média de idade dos participantes esteve entr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
0
0
12

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 16 publications
1
0
0
12
Order By: Relevance
“…However, a review performed in Germany with the main QOL studies using the QLQ-C30 to evaluate the pre-and post-HSCT (11) , and another review performed in Chicago (USA) that compared the QOL of patients undergoing autologous and allogeneic HSCT in 105 participants with cancer, showed the patients' age was between 40 and 50 years (12) , which differs from the present study findings. The marital status and number of children in this study corroborate data found in national and international literature, i.e., patients with hematological malignancies are married or in a common-law marriage and have one to three children (12)(13)(14)(15)(16) . In a study on the bond between cancer patients and their families, it was observed that the main companions of patients with neoplasia are children, spouses and parents, and family involvement is critical during the disease process.…”
Section: Discussionsupporting
confidence: 87%
“…However, a review performed in Germany with the main QOL studies using the QLQ-C30 to evaluate the pre-and post-HSCT (11) , and another review performed in Chicago (USA) that compared the QOL of patients undergoing autologous and allogeneic HSCT in 105 participants with cancer, showed the patients' age was between 40 and 50 years (12) , which differs from the present study findings. The marital status and number of children in this study corroborate data found in national and international literature, i.e., patients with hematological malignancies are married or in a common-law marriage and have one to three children (12)(13)(14)(15)(16) . In a study on the bond between cancer patients and their families, it was observed that the main companions of patients with neoplasia are children, spouses and parents, and family involvement is critical during the disease process.…”
Section: Discussionsupporting
confidence: 87%
“…As ocupações do paciente com câncer são afetadas devido à nova rotina de consultas médicas e sessões de quimioterapia, necessárias durante o tratamento (SOUSA; BARRETO; GOMES, 2018). Além disso, receber um diagnóstico de câncer pode causar na pessoa acometida por essa doença sentimentos de medo, angústia, preocupação e temor da finitude, exigindo também readaptações das atividades que desempenhava em sua rotina (BATISTA; MATTOS; CALEFI et al, 2014;BARRETO;GOMES, 2018).…”
Section: Discussionunclassified
“…Isto evidencia o câncer como um problema relevante para os órgãos de saúde (INCA, 2019). Estudos (BATISTA;MATTOS;CALEFI et al, 2014;FARIA;DE CARLO, 2015;JOAQUÍN-MINGORANCE et al, 2019) apontam que dentre os possíveis impactos do diagnóstico e tratamento do câncer, destaca-se a perda da capacidade funcional, o afastamento das atividades do trabalho, com consequente diminuição de renda, a perda da autoestima, diminuição do autocuidado e desorganização da vida familiar.…”
Section: Introductionunclassified
“…De acordo com o perfil dos pacientes acometidos por neoplasias onco-hematológicas mais prevalentes no setor de internação, no presente estudo observou-se a predominância da leucemia (42%), seguida de linfoma (36,8%) e mieloma (21%), corroborando os achados de Calefi et al 19 em estudo realizado com 16 sujeitos, no Setor de Quimioterapia de Alto Risco e Ambulatório, em um Hospital de Ensino em Curitiba-PR, apontando a incidência de 80% de leucemias e 20% entre linfomas e mieloma múltiplo. O sexo feminino no presente estudo obteve frequência de 57,9%, havendo equilíbrio na incidência de leucemia entre homens e mulheres, em contraste com outros autores 20 que apresentam resultados maiores na prevalência leucêmica no sexo feminino.…”
Section: Discussionunclassified